The Existence of Digital Marketing in Supporting Brand Awareness and Consumptive Behavior: A Review with Systematic Literature Review (SLR) Method - Wahyudi, Eko Juni Wahyudi; Sudarmiatin, Sudarmiatin (IJBLE Scientific Publications Community Inc., 2024)
The development of digital marketing today has the potential to change economic patterns in Indonesia, changes in economic patterns can be in the form of an increase in people's purchasing power and changes in people's consumptive behavior. It is necessary for someone to know and learn this digitalization era to accelerate economic growth. Currently, digital marketing is a crucial element in business marketing strategies. In addition, digital marketing plays an important role in the development of MSMEs, one of which is MSMEs in the creative economy. Marketing strategies with digital marketing tend to have higher revenue growth compared to those that do not use digital marketing as a marketing strategy. This research uses the Systematic Literature Review (SLR) method. The research data comes from various national and international journals that examine the existence of digital marketing. The research found that there are 12 international journals that review the existence of digital marketing. The conclusion of this research shows that the existence of digital marketing has an important